Evaluasi Peraturan Daerah Kota Pekanbaru Nomor 9 Tahun 2014 Tentang Pengelolaan Pasar Rakyat, Pusat Perbelanjaan dan Toko Swalayan pada Dinas Perdagangan dan Perindustrian (Studi Kasus Perencanaan Fisik Pasar Sail di Kecamatan Sail) - Elly Nielwaty (JOELS: Journal of Election and Leadership, 2021)
This research discusses the evaluation of the Pekanbaru City Regional Regulation Number 9 of 2014. Every people's market must meet the requirements starting from the supporting facilities and facilities that must exist in the people's market according to those already in the policy, while at Sail Market there are supporting facilities and facilities which are not available or many are not functioning due to lack of maintenance from the manager. The theory used is Riant Nugroho's evaluation theory which suggests an evaluation of policy performance. The place of this research is the Department of Trade and Industry of Pekanbaru City and Sail Market . The purpose of this study is to evaluate the Regional Regulation Number 9 of 2014 on the physical planning of Sail market. This research uses a descriptive qualitative method, this method is used to describe how the Pekanbaru City government manages and supervises the people's market, especially the Sail Market. The results of this study conclude that the Pekanbaru City government in dealing with people's markets managed by third parties to create a decent, safe and healthy people's market according to the provisions of Regional Regulation No. 9 of 2014 has not been effective. The Department of Trade and Industry has not been able to carry out its duties and functions as the agency responsible for managing the people's market. This is because the current condition of Sail market is that there are many supporting facilities and facilities that do not exist.